Proposed Marketing Strategy For Tempo Newspaper On Facing Digitization Era - Gratiano, Antonio; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2015)
Abstract.Indonesia has a rapid growth of internet users. Moreover, technology development makes newspaper industry should adapt with the situation. Tempo Inti Media is one of the leading media industries in Indonesia, which has long served its readers with the news from Tempo Newspaper which has uniqueness in journalistic style; tend to criticize sharply and straight to the point. Nowadays, as a part of Tempo Media Group business line, Tempo Newspaper entering the phase where the newspaper sales are declining, but in the other hand Tempo.co as an online news source has a massive growth.External and internal analysis was conducted to determine consumer behavior and the impact and implications of technology for the newspaper industry, especially the Tempo newspaper. It also conducted a field study to determine the level of importance and the quality performance of Tempo Newspaper, Tempo Website, Newspaper Competitors and Competitor Websites from a consumer standpoint. The outcome of the field study is also used to make Importance-Performance Matrix (IPM)to know the variables of Tempo Newspaper that need to be improved.The results of the analysis of field studies, it is known that some of the variables of Tempo Newspaper can be improved but overall Tempo should slowly move into the online platform because of the perspective of customers, today newspaper is considered unable to meet consumer needs for update news. Besides, it should also focus on improving Tempo website because based on the field study to Tempo Newspaper readers, although customers prefer to read through online media, but not necessarily readers will open Tempo website because there are other competitors who offers better quality than Tempo website.The proposed improvement quality of Tempo Newspaper and Tempo website is expected not only to increase the newspaper revenue but also to add customers interest to access Tempo website so has competitiveness of its competitors.Keywords: Tempo Newspaper, Tempo website, quality, consumer behavior